Analyzing Socialized Tuition Fee Structures in Basic Education: Impacts and Sustainability: Analyzing Socialized Tuition Fee Structures in Basic Education: Impacts and Sustainability - Daryl Quinco; Meredith Embuscado; Benedicto Saligan; Antolin Alcudia (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study delves into the socioeconomic landscape of the La Salle University Integrated School (LSU-IS) and its broader context within Ozamiz City, focusing on the affordability and accessibility of education for students from diverse economic backgrounds. The rationale for this research stems from the recognition of disparities in household incomes and their implications on education spending, particularly in a region where public school availability varies across grade levels. A quantitative data analysis of household incomes and education spending patterns with insights from surveys and interviews. The results revealed a predominant presence of middle-income households among LSU-IS students, alongside significant percentages falling below the poverty line or within the low-income bracket. This diversity underscores the necessity for a nuanced tuition framework that accounts for varying financial capacities. Ozamiz City's educational infrastructure was also scrutinized, highlighting a disparity in public school provision between elementary and high school levels. While elementary schools are relatively well-distributed across barangays, public high schools are limited in number, potentially hindering students' educational progression. The study's conclusion emphasizes the need for a flexible and equitable tuition structure at LSU-IS, aligning fees with household incomes while ensuring financial sustainability for the institution. Strategies such as tiered tuition systems, optimized class sizes, and external sponsorships are recommended to address financial challenges and enhance inclusivity in education. These findings contribute to ongoing discussions on education accessibility and affordability, advocating for tailored approaches that empower students from all economic backgrounds to pursue quality education.